Analisis Hygiene Sanitasi Kapal Di Wilayah Pelabuhan Tanjung Perak Surabaya - KHULIYAH CANDRANING DIYANAH; Akhmad Abu Khanifah; Aditya Sukma Pawitra (Sanitasi: Jurnal Kesehatan Lingkungan, 2021)
Sanitation checks are carried out to assess all sanitary conditions related to the presence of environmental risk factors on the ship. This study aims to analyze ship sanitation hygiene in the Port of Tanjung Perak, Surabaya City in August 2019. This research was an observational study with a cross-sectional approach. Data collection qualitatively by observation following the ship sanitation inspection and interview forms. A sample of 10 ships consisting of 9 cargo ships and 1 passenger ship in which the sample category is a ship that docked or berthed in the Tanjung Perak Port area of  Surabaya City and has expired the sanitation certificate of the ship. Data analysis using descriptive methods. The results of ship sanitation hygiene checks with Permenkes Number 40 of 2015 concerning Ship Sanitation Certificate. Nine out of ten vessels inspected (90%) had sanitary hygiene that met the requirements, while 1 ship (10%) did not meet the sanitation hygiene requirements, namely passenger ships. Passenger ship parts that do not meet the requirements are kitchen, pantry, warehouse, and sleeping room. There is a vector of cockroaches and flies, as well as signs of rodent life (rats). Vessels resting at the port of Tanjung Perak have fulfilled hygiene and sanitation requirements based on Permenkes Number 40 of 2015 concerning Ship Sanitation Certificate.